2023
DOI: 10.1088/1674-1137/acd366
|View full text |Cite
|
Sign up to set email alerts
|

Charge-changing cross section measurements of 300 MeV/nucleon 28Si on carbon and data analysis*

Abstract: Charge-changing cross section ($\sigma_{\text{cc}}$) measurements via the transmission method have made important progress recently aiming to determine the charge radii of exotic nuclei. In this work, we report a new $\sigma_{\text{cc}}$ measurement of 299(9) MeV/nucleon $^{28}$Si on carbon at the second Radioactive Ion Beam Line in Lanzhou (RIBLL2) and describe the data analysis procedure in detail. This procedure is essential to evaluate the systematic uncertainty in the transmission method.
The dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that the charge-changing cross section measurements can be used to determine the EoS of nuclear matter with mirror nuclei [97]. This method can also be employed to investigate the charge radii of exotic nuclei [98] and the isospin interactions [99].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the charge-changing cross section measurements can be used to determine the EoS of nuclear matter with mirror nuclei [97]. This method can also be employed to investigate the charge radii of exotic nuclei [98] and the isospin interactions [99].…”
Section: Resultsmentioning
confidence: 99%